Association between Serum Total Cholesterol Levels and Unfavourable Outcome in Patients with Spontaneous Intracerebral Hemorrhage - Akram, Samra; Sohail, Sharjeel; Ahmed, Nauman; Saleem, Mohiuddin; Asad, Hira (Indus Journal of Bioscience Research, 2025)
Background: To determine the association between low serum total cholesterol levels and unfavorable outcomes in patients with spontaneous ICH. Methods: This prospective cohort study was conducted in the Department of Neurosurgery, Shaikh Zayed Hospital, Lahore, from February 2025 to June 2025. A total of 200 patients aged 30–90 years presenting within 72 hours of ICH onset were enrolled and categorized into two groups based on fasting serum TC levels: exposed group (<160 mg/dL) and unexposed group (≥160 mg/dL). Neurological deficit at admission was objectively graded using the National Institutes of Health Stroke Scale (NIHSS) to determine stroke severity, and functional outcome was measured using the Modified Rankin Scale (mRS). Data were analyzed using SPSS version 21, and relative risk (RR) with 95% CI was calculated to assess association, significance was defined as a p-value less than or equal to 0.05. Results: Patients with low TC had a higher frequency of severe stroke (46% vs. 28%, p=0.009) and unfavorable outcome (61% vs. 38%, p=0.001). The relative risk of unfavorable outcome in the low cholesterol group was 1.60 (95% CI: 1.21–2.13). The association remained significant after stratification by age, gender, hypertension, and diabetes. Conclusion: Low serum total cholesterol levels are significantly associated with greater stroke severity and increased risk of unfavorable outcomes in patients with spontaneous ICH. Serum cholesterol may serve as an independent prognostic biomarker in acute ICH.